GREEN MARKETING AND ITS EFFECT ON PURCHASE DECISIONS OF CAR LOW COST GREEN CAR (LCGC) IN KARAWANG - N. , Neni Triana; Astuti Widi Rahayu, Ade; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
The concept of Green Marketing is a concept that resembles the concept of marketing mix which refers to satisfaction, needs, desires and desires of customers to get a product or service. The difference between Green Marketing and the conventional mix concept is customer that the intended will be involved in environmental preservation and maintenance. The relationship customer in preserving the environment creates an opportunity for world automotive companies to increase sales by implementing the concept Green Marketing. The issue of global warming in the automotive sector today can be reduced by starting to use LCGC (Low Cost Green Car) products, this study aims to find out how the phenomenon of Green Marketing in the automotive sector has an effect on selling cheap and environmentally friendly cars that have low specifications, more economical fuel because it uses a small engine size cc (centric cubic)with the aim of reducing high exhaust emissions. Descriptive review results prove Green Marketing to be an alternative strategy to help the image company’s, but also provide value more to the company’s business. Implementing a strategy green marketing requires a fundamental, comprehensive, and integrated approach in all aspects of marketing, including the overall marketing mix with 4P (Price, Product, Place and Promotion).